Magnetic actuators - Howe, D. (Sensors and actuators. A. Physical., 2000)
The subject of magnetic actuators is very broad, and encompasses various technologies, as well as a wide range of magnetic circuit topologies and performance characteristics, for an ever-increasing spectrum of applications in all market sectors. Magnetic actuators can be rotary or linear, and can have continuous or limited motion, the basic classes being moving-coil, moving-iron and moving-magnet. Within these, the airgap length may either remain constant or vary with displacement, and while the majority of such actuators have only one degree-of-freedom, systems are emerging which are capable of providing multiple degrees-of-freedom of controlled motion. In view of the breadth of the subject, the paper focuses on research which is being undertaken in the Electrical Machines and Drives Group at the University of Sheffield on some specific magnetic actuation systems. These include: • Aerospace—electromechanical and electro-hydraulic actuators for flight control surfaces, • Automotive—short-stroke actuators, for applications such as high-speed diesel fuel injector control valves; active and passive magnetic bearing actuation systems for electric vehicle flywheel energy storage units, • Industrial—long stroke linear motors for high-speed packaging and manufacturing applications, • Healthcare—reciprocating linear actuators for resonant electro-mechanical systems, such as positive-displacement diaphragm air-compressors, • Computer—multi-degree-of-freedom spherical actuators for force-feedback joysticks, manipulators etc. As will be highlighted, much of the research involves the application of high-energy rare-earth permanent magnets, which have facilitated the development of new and improved performance magnetic actuators.